A grammar of Kukama-Kukamiria : a language from the Amazon - Vallejos, Rosa (Brill's studies in the indigenous languages of the Americas, 2016)
This book offers a comprehensive description of Kukama-Kukamiria, spoken by about 1000 elders in the Peruvian Amazon. This grammar comes from fifteen years of fieldwork; it is organized in seventeen chapters dealing with phonology, morphology, syntax and discourse phenomena.